2022
DOI: 10.1002/alz.12795
|View full text |Cite
|
Sign up to set email alerts
|

Association of liver fibrosis with cognitive test performance and brain imaging parameters in the UK Biobank study

Abstract: Introduction:We hypothesized that liver fibrosis is associated with worse cognitive performance and corresponding brain imaging changes. Methods:We examined the association of liver fibrosis with cognition and brain imaging parameters in the UK Biobank study. Liver fibrosis was assessed using the Fibrosis-4 (FIB-4) score. The primary cognitive outcome was the digit symbol substitution test (DSST); secondary outcomes were additional executive function/processing speed and memory tests. Imaging outcomes were hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 50 publications
3
23
1
Order By: Relevance
“…Yet, in contrast to our results, the prior UK Biobank study also demonstrated an association of fibrosis with lower hippocampal volume [12]. The latter discrepancy may stem from differences in ascertainment of liver fibrosis, which was done indirectly through serum-based markers in the former study.…”
Section: Of 11contrasting
confidence: 99%
See 2 more Smart Citations
“…Yet, in contrast to our results, the prior UK Biobank study also demonstrated an association of fibrosis with lower hippocampal volume [12]. The latter discrepancy may stem from differences in ascertainment of liver fibrosis, which was done indirectly through serum-based markers in the former study.…”
Section: Of 11contrasting
confidence: 99%
“…In turn, patients with NASH are prone to disease progression to various stages of fibrosis, as well as cirrhosis and eventually hepatocellular carcinoma [9]. Mounting evidence demonstrates an association of liver fibrosis with an increased risk of stroke [10], poor cognitive function [11][12][13], and higher rates of incident dementia [14]. Furthermore, liver fibrosis was observed to be associated with lower total brain and hippocampal volumes in a large sample of the UK Biobank study [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012). In a newly published cohort research employing the UK Biobank, fibrosis and cirrhosis of the liver were strongly linked to an elevated risk of incident dementia, cognitive impairment, and cognitive‐related brain structures (Parikh, Kamel, Zhang, Gupta, et al., 2022; Parikh, Kamel, Zhang, Kumar, et al., 2022). Liver fibrosis is believed to lead to liver cirrhosis which, in turn, leads to hepatic encephalopathy, the pathophysiology of which involves astrocyte and neuronal modifications caused by inflammation, dietary and metabolic variables, ammonia build‐up, and neurosteroid‐induced GABAergic system activation, leading to the pathological changes that are observed in AD (Butterworth, 2019; Rose et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Parikh et al. proposed that liver fibrosis is associated with a higher risk of dementia, cognitive impairment, and cognitive‐related abnormal brain structure (Parikh, Kamel, Zhang, Gupta, et al., 2022; Parikh, Kamel, Zhang, Kumar, et al., 2022). Although the results of these studies have provided some evidence of the potential relationship between liver function and cognitive function, the underlying link remains unclear.…”
Section: Introductionmentioning
confidence: 99%